Yarrowia lipolytica as a promising cell factory for microbial production of value-added nutraceuticals - Lee, Soseon; Lee, Ju Hyeon; Park, Hyun June; Baek, Seung-Ho (Frontiers in Bioengineering and Biotechnology, 2025)
The oleaginous yeast Yarrowia lipolytica has emerged as a powerful chassis for the sustainable production of high-value nutraceuticals. Its innate metabolism, characterized by a high flux towards the key precursor acetyl-CoA, makes it an ideal host for synthesizing complex molecules like carotenoids, flavonoids, and specialty lipids. This review summarizes recent progress in engineering Y. lipolytica cell factories, focusing on the synergistic application of metabolic engineering and synthetic biology. Key strategies discussed include enhancing precursor supply, redirecting metabolic flux away from competing pathways, and optimizing heterologous gene expression. We highlight the use of advanced tools like organelle compartmentalization to improve reaction efficiency and biosensor-driven screening to accelerate strain development. Furthermore, systems biology approaches utilizing multi-omics data are proving crucial for identifying novel engineering targets and overcoming metabolic bottlenecks. This review consolidates these advancements and discusses future perspectives for creating robust, industrially-relevant Y. lipolytica platforms for the bio-based economy.